2021
DOI: 10.3390/ani11061736
|View full text |Cite
|
Sign up to set email alerts
|

Milk Lactose as a Biomarker of Subclinical Mastitis in Dairy Cows

Abstract: Bovine subclinical mastitis can cause great harm to dairy herds because of its negative impact on milk production and quality and cow health. Improved diagnostic tools are needed to maximise the control of subclinical mastitis distribution and ensure the high quality of milk as an industrial product. Between 2015 and 2020, seventy-two dairy herds were screened for bovine subclinical mastitis causative agents to identify the relationship between seasons, lactose levels and subclinical mastitis infection. The pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 38 publications
1
38
0
1
Order By: Relevance
“…As far as our experiment is concerned, the ruminal degradability of soybean peptides needs further investigation. Milk lactose synthesis is influenced by udder health ( 48 ), metabolism, and energy balance in dairy cows ( 49 ). Propionate accounts for half of the hepatic glucose output, which in turn accounts for two-thirds of the glucose required for milk lactose synthesis ( 50 , 51 ).…”
Section: Discussionmentioning
confidence: 99%
“…As far as our experiment is concerned, the ruminal degradability of soybean peptides needs further investigation. Milk lactose synthesis is influenced by udder health ( 48 ), metabolism, and energy balance in dairy cows ( 49 ). Propionate accounts for half of the hepatic glucose output, which in turn accounts for two-thirds of the glucose required for milk lactose synthesis ( 50 , 51 ).…”
Section: Discussionmentioning
confidence: 99%
“…Having said that, the higher milk lactose in the control and 12 hG groups compared with the 24 hG group could be explained by the abovementioned reason. Moreover, Antanaitis et al, [ 42 ] have reported that the increase in milk lactose has a strong negative linear relationship with SCC. They underlined the importance of milk lactose as an indicator of subclinical mastitis showing that the increase in lactose levels in cow’s milk was most closely associated with a decrease in the prevalence of subclinical mastitis pathogens such as S. agalactiae , S. aureus and other Streptococci .…”
Section: Discussionmentioning
confidence: 99%
“…A saúde do úbere, balanço energético negativo e condições metabólicas desfavoráveis estão relacionadas ao aumento do número de CCS e baixos níveis de lactose. Ainda, consta que o sucesso reprodutivo do animal está relacionado positivamente ao nível de lactose no leite (ANTANAITIS et al, 2021).…”
Section: Apresentaçãounclassified